Impact of exercise on outcomes among Chinese patients with Crohn’s disease: a mixed methods study based on social media and the real world - Shaopeng Sun; Jiajia Chen; Mingxu Zheng; Mi Zhou; Xue Ying; Yanjie Shen; Yibo Hu; Keying Ni; Yihong Fan; Bin Lv (BMC Gastroenterology)
Abstract Objective The effects of exercise on the health of people with Crohn’s disease (CD) remain unclear. This study aimed to explore the perspective of Chinese CD patients on exercise and the quantitative relationship between exercise and patient-reported outcomes. Methods This study used a mixed methods design consisting of three components. (1) Big data were mined from social media, and latent Dirichlet allocation (LDA) was used to perform cluster analysis on topics related to physical exercise. (2) A seven-step Colaizzi process was used to conduct semistructured interviews to obtain in-depth information about exercise. (3) A cross-sectional study was performed to examine this relationship using the Global Physical Activity Questionnaire (GPAQ) and Patient-reported Outcome Measurement Information System (PROMIS). Results LDA yielded a total of 1536 exercise-related posts; eight topics concerning CD patients were obtained through clustering (peer support, exercise therapy, diet, fatigue, exercise type, intestinal symptoms, body constitution and mental health), and 11 patients were interviewed to validate the results of LDA and explore the insight of Chinese CD. We identified two themes: the effects of exercise on people with CD and factors that promote and hinder exercise. A total of 119 patients with CD were surveyed. Considering confounding factors such as disease activity and medication, moderate-intensity recreational PA increased patients’ physical function and improved anxiety, depression, fatigue, pain intensity, and pain impact (all p < 0.05). In contrast, high-intensity work may lead to anxiety, depression, fatigue, pain, and pain effects (all p < 0.001). In addition, sedentary behaviour may lead to depression (p = 0.006). Conclusion Patients with CD tend to seek guidance on exercise through social media, and they generally believe that exercise is beneficial, especially for their psychological and spiritual health, despite difficulties in exercising. Physical activity may be an important factor affecting patients’ psychological health. Lay summary Crohn’s disease has a profound impact on mental and emotional health, reducing patients’ quality of life. Exercise is a good habit that can enhance mental, emotional and social health, but there is currently no standard exercise program for patients with Crohn’s disease. The exercise experience of Chinese patients with Crohn’s disease can be helpful in formulating exercise plans.